DESIGN AND SIMULATION OF A SCADA - CONTROLLED GREENHOUSE FOR OPTIMIZED ROSE CULTIVATION (Balkan Journal of Applied Mathematics and Informatics, 2025)
This study presents the design and simulation of a SCADA system for monitoring and automated control of environmental and operational parameters in a rose greenhouse. Development of the SCADA system within this project was supported by the Ignition platform – a modern, modular and industrially oriented software solution from Inductive Automation, which enables the creation of SCADA, HMI and IoT applications. Careful design considerations were applied to ensure that the virtual model accurately reflects actual operational conditions. By modifying the parameters, the system can be easily adapted to manage different types of plants. The application of SCADA technology in horticulture enables advanced resource optimization strategies, resulting in enhanced greenhouse production outcomes, operational performance and efficiency. By combining design and simulation, this study highlights the potential of virtual SCADA systems as tools for planning, analysis, and development of efficient solutions for process management in contemporary horticulture. While the simulation confirms that the design meets all specified requirements, real greenhouse implementation would require modifications or adjustments to the control logic to adapt to actual operational conditions.
Keywords: Tag, alarm, temperature, soil moist, air humidity, script